An exploration into the conditions enabling and constraining the implementation of quality assurance in higher education: the case of a small comprehensive university in South Africa - Masehela, Langutani Meriam (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2015)
At an international level, demands for accountability in respect of the quality of teaching and learning in higher education are increasing. This is also the case in South Africa. The response to these demands has taken the form of the introduction of quality assurance systems to higher education. In South Africa, a formal national external quality assurance was introduced to the higher education system in 2001 as a result of the establishment of the Higher Education Quality Committee. The Higher Education Quality Committee is a standing committee of the South African Council on Higher Education. Like other quality assurance agencies across the world, the Higher Education Quality Committee has the responsibility for i) auditing institutions of higher education and ii) accrediting learning programmes. The first cycle of institutional audits ran from 2004 until 2011. As quality assurance was introduced to the higher education system and the first cycle of institutional audits began, universities in South Africa developed policies and procedures intended to assure quality in three areas of their core functioning: research, teaching and learning and community engagement. The University of Venda, which is the focus of the study on which this thesis is based, was no exception. As a practitioner in the Centre for Higher Education Teaching and Learning at The University of Venda, it was my observation that the policies and procedures intended to assure quality in teaching and learning were not always implemented by academic staff members. This was in spite of poor student performance data which raised questions about the quality of the teaching and learning processes in place. The study underpinning this thesis was designed to explore this phenomenon. More specifically, it aimed to identify the conditions enabling and constraining the implementation of policies and procedures in two Schools in the University: the School of Health Sciences and the School of Human and Social Sciences. In order to explore these conditions, I adopted Roy Bhaskar's Critical Realism as an under-labouring philosophy for the study. Critical realism posits a view of reality comprising three strata, none of which can be reducible to the other. The first of these strata is termed the level of the Empirical and consists of the experiences and observations which become apparent to us through the senses. The second layer, the Actual, consists of events from which these experiences and observations emerge. Underpinning both of these layers is a further layer, the Real, which is not accessible by empirical means and which consists of structures and mechanisms which generate both events at the level of the Actual and experiences and observation at the level of the Empirical. The design of my study sought to reach this deepest layer of reality to identify these mechanisms. Bhaskar's critical realism is philosophy which needs to be operationalized using substantive, or explanatory, theory. For this purpose, I drew on Margaret Archer's social realism. The design on my study drew on case study methodology and involved in-depth interviews with members of the two Schools which each formed cases within the more overarching case of the University itself. In addition to these interviews, I analysed a range of institutional documents related to the assurance of quality in teaching and learning. The exploration of enabling and constraining conditions at the level of the Real allow me to make a series of recommendations in the final Chapter of my thesis intended to enhance the quality assurance system introduced to the University.
Keywords: University of Venda -- Evaluation; Education, Higher -- South Africa -- Evaluation; Universities and colleges -- South Africa -- Auditing; Quality assurance -- South Africa; Quality assurance -- Standards -- South Africa; Universities and colleges -- South Africa -- Evaluation; Educational accountability -- South Africa; Education, Higher -- Standards -- South Africa; Educational evaluation -- South Africa; Critical realism; Social realism